FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN UPAYA KESIAPSIAGAAN KARYAWAN BAGIAN PRODUKSI DALAM MENGHADAPI BAHAYA KEBAKARAN DI PT SANDANG ASIA MAJU ABADI - Laila Fitriana; Suroto Suroto; Bina Kurniawan (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Preparedness is a series of activities that are conducted to anticipate disasters by organizer and do appropriate steps effectively and efficiently. The garment industry is a workplace with third level of fire classification that has high amount and high flammability. Recorded in a few times ago, a small fire happened in PT Sandang Asia Maju Abadi was caused by an electrical short circuit. This research is purposed to analyze the factors which are related to preparedness effort of fire hazard of production employees in PT Sandang Asia Maju Abadi. Type of this research is analytical by cross sectional approach. Samples in this research are 96 from 2.043 production employees with proportionate stratified random sampling technique. Data is collected by questionnaire from respondents and for supporting data it needs observation of fire protection facilities by observation checklist. Based on the results of research by using Chi-square, the dependent variables are work time, the knowledge, availability of fire protection, fire fighting training, and control from occupational safety and health officer. Meanwhile, the independent variables are age, gender, level of education, and attitudes. The researchers suggest to the company to increase of fire fighting training participants, information during the briefing that related to fire, and improve some fire protection facilities.